A Comparison of Laparoscopies and Laparotomies for Radical Hysterectomy in Stage IA1-IB1 Cervical Cancer Patients: A Single Team With 18 Years of Experience - Qin, Meng; Siyi, Li; Huang, Hui-Fang; Li, Yan; Gu, Yu; Wang, Wei; Shan, Ying; Yin, Jie; Wang, Yong-Xue; Cai, Yan; Chen, Jia-Yu; Jin, Ying; et al. (Frontiers in Oncology, 2020)
Objective To investigate the safety and efficacy of abdominal radical hysterectomy (ARH) and laparoscopic radical hysterectomy (LRH) in managing early-stage cervical cancer. Methods This retrospective study comprised patients with FIGO stage IA1 with lymphovascular space invasion (LVSI), IA2, and IB1 cervical cancer who underwent radical hysterectomy performed by a single gynecologic oncology team at Peking Union Medical College Hospital from 2000–2018. The clinicopathological characteristics, surgical outcomes, and survival outcomes were compared between the two groups. Results The ARH and LRH groups consisted of 84 and 172 patients, respectively. The 5-year progression-free survival (PFS) rates were 89.3 and 95.9% in the ARH and LRH groups (P = 0.122, adjusted HR = 0.449, 95% CI: 0.162–1.239), respectively, while the 5-year overall survival (OS) rates were 95.2 and 98.8%, respectively (P = 0.578, adjusted HR = 0.650, 95% CI: 0.143–2.961). The presence of more than two comorbidities led to poor OS (P = 0.011). For patients with a BMI greater than 24 kg/m2, LRH was associated with better PFS (P = 0.039). Compared with ARH, LRH was associated with a shorter operation time (248.8 vs. 176.9 min, P < 0.001), less blood loss (670.2 vs. 200.9 ml, P < 0.001), and lower postoperative ileus rates (2.4% vs. 0%, P = 0.042). No significant differences were observed in PFS and OS between 2006–2012, 2013–2015, and 2016–2018 in the LRH group (P = 0.126 and P = 0.583). Conclusion Compared with ARH, LRH yields similar survival and improved surgical outcomes in patients with early-stage cervical cancer. LRH is not inferior to ARH for select cervical cancer patients treated by a single team with adequate laparoscopy experience.